2022
DOI: 10.1002/nop2.1211
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of burnout and its dimensions among mental health workers during the COVID‐19 pandemic

Abstract: Aim To examine the demographic and work characteristics of mental health workers associated with burnout during the COVID‐19 epidemic and to examine the relationship between burnout and humanistic care ability. Design Online cross‐sectional design. Methods 270 mental health workers in Chongqing, China, were recruited via WeChat from 1 to 31 December 2020. Online self‐administered questionnaires were used to collect data. Data were analyzed by t‐tests and one‐way analyses of variance, Pearson's correlation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 61 publications
(70 reference statements)
0
16
2
Order By: Relevance
“…STS and PTSD are highly overlapping syndromes since STS in MHWs is characterized by symptoms of reliving, avoidance, and hyperarousal in response to the traumatized patients with whom they are empathically engaged [ 30 ]. According to our findings, traumatic impact when dealing with secondary exposure to stressful events is aggravated due to FCV-19 in both MHWs and HCWs [ 17 , 21 , 25 , 32 , 56 , 57 ]. However, we found that FCV-19 explained a significant yet relatively low percentage of STS variation.…”
Section: Discussionmentioning
confidence: 77%
“…STS and PTSD are highly overlapping syndromes since STS in MHWs is characterized by symptoms of reliving, avoidance, and hyperarousal in response to the traumatized patients with whom they are empathically engaged [ 30 ]. According to our findings, traumatic impact when dealing with secondary exposure to stressful events is aggravated due to FCV-19 in both MHWs and HCWs [ 17 , 21 , 25 , 32 , 56 , 57 ]. However, we found that FCV-19 explained a significant yet relatively low percentage of STS variation.…”
Section: Discussionmentioning
confidence: 77%
“… 2021 ) or only experienced mild burnout (Zhu et al . 2022 ). An additional five studies found that MHWs who worked remotely and conducted online therapy experienced increased fatigue during online therapy, also referred to as ‘zoom fatigue’ (Aafjes‐van Doorn et al .…”
Section: Resultsmentioning
confidence: 99%
“…Occupational well-beingOutcomes related to occupational well-being of MHWs were reported across 30 studies. There were numerous reports of moderate-to-high levels of burnout, exhaustion, and fatigue amongst One study found that burnout was highest when work changes were most profound(Sklar et al 2021), another reported no demonstrable change in burnout levels in majority of MHWs(Steidtmann et al 2021) or only experienced mild burnout(Zhu et al 2022). An additional…”
mentioning
confidence: 99%
“…It reported age, family income, daily working hours, workload, insufficient protection working in a high-quality hospital, having more years of work experience, having more night shifts and fewer paid vacation days, etc. were associated with burnout among HPs during the pandemic in China ( 14 16 ). Although studies observed a positive association between workplace violence and burnout ( 17 , 18 ), no study reported whether workplace violence affected burnout differently during COVID-19 in China.…”
Section: Introductionmentioning
confidence: 99%